2011
DOI: 10.1103/physrevstab.14.102803
|View full text |Cite
|
Sign up to set email alerts
|

Nonintercepting electron beam size monitor using optical diffraction radiation interference

Abstract: In recent years, the use of diffraction radiation (DR), emitted when a charged particle beam passes\ud through a rectangular slit, has been proposed and successfully tested as a nonintercepting diagnostic of\ud high brightness beams. However, some problems related to the control of the particle trajectory through\ud the slit still remain. If an additional slit is placed in front of the first one, at a distance shorter than the\ud radiation formation length, interference between the forward diffraction radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…This setup is able to clearly estimate the emittance, the angular divergence and even the position of the beam inside the slit, as we already demonstrated in [7]. In this paper we further extend our study comparing the data obtained under the same beam condition but observing different wavelengths or polarization states.…”
Section: Odrisupporting
confidence: 63%
See 2 more Smart Citations
“…This setup is able to clearly estimate the emittance, the angular divergence and even the position of the beam inside the slit, as we already demonstrated in [7]. In this paper we further extend our study comparing the data obtained under the same beam condition but observing different wavelengths or polarization states.…”
Section: Odrisupporting
confidence: 63%
“…An introduction and explanation of the ODRI theory can be found in [7]. Here we report just the fundamental details.…”
Section: Odrimentioning
confidence: 99%
See 1 more Smart Citation
“…It should be underlined that after some angle the radiation will start to reflect again from the lower (or upper) half-plane of the second slit, but in our work we do not consider so big angles. In the paper [5] the research for the system with collinear slits was performed and it was shown that additional slit in the system can dramatically change DR angular distribution. In paper [6] changes in DR angular distribution, caused by shifting the slits were investigated.…”
Section: Theorymentioning
confidence: 99%
“…For this reason the techniques based on Diffraction Radiation (DR) [1,2] were proposed and tested [3,4], adopting a single-slit geometry. In order to avoid some problems connected with this geometry, such as the impossibility to separate effects caused by both beam size and beam offset within the slit, a two slits system was proposed [5] and experimentally tested. Since in this system an additional slit is introduced, it becomes necessary to investigate effects caused by new parameters, which appear due to the second slit.…”
Section: Introductionmentioning
confidence: 99%